A sea is brewing - Mama, Sibongakonke (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of poems that draws on the complexity of not belonging in places, with people, or within families. I engage my own alienation as well as that of my parents, black people generally, and women in particular. I take inspiration from Uruguayan poet Fabián Severo's autobiographical long poem, Night in the North, which chronicles the poet's experience of growing up in linguistic and cultural borderlands. I am also influenced by Chilean poet Carmen GarcÃa's ability to move between the concrete and the abstract in translations of her poems from the collection Gotas sobre loza frÃa. As much as my poems traverse a metaphysical space, they are also set in concrete places "“ Tutura, Gcuwa, Johannesburg, and Cape Town. Like Chilean artist Cecilia Vicuña's Spit Temple, I move between the physical and spiritual realms for a better understanding of my estrangement. I also draw on South African poet Mangaliso Buzani's book, a naked bone, for its fluid combination of line and prose poetry. I write in isiXhosa and English as a reflection of my mixed cultural and linguistic existence. I seek to harness rhythm and harmony, as well as the quiet, between words.
Keywords: Creative writing (Higher education) -- South Africa; Xhosa poetry 21st century; South African poetry (English) 21st century; Psychic trauma in literature; Women in literature; Diaries -- Authorship; Books Reviews